Perceptions of Classroom Interactions and Students’ Thriving in Hybrid and Blended Learning: A Multi-Group Analysis - Ani Cahyadi; Hendryadi Hendryadi; Rimi Gusliana Mais (Dinamika Ilmu, 2022)
This study aims to uncover the relationship between the quality of class interaction in learning activities and student thriving in the two methods (hybrid and blended) used in the past year. Using a sample of 112 students selected through a purposive approach, data were collected using a questionnaire at the end of the semester in 2021/2022. Partial least square structural equation modeling (PLS-SEM) with multi-group analysis (MGA) was applied to test the model. The study's results provide empirical support regarding the relationship between classroom interaction quality and student perceived thrive (vitality and learning) in both learning modes. Finally, a comparison of the effects based on MGA identified that the quality of classroom interaction was more effective on vitality than blended learning compared to hybrid learning. While regarding perceived learning, the dominant effect of classroom interaction is more effective in blended learning mode.